Réponses

Meilleure réponse !
2014-03-08T23:49:40+01:00
Bonsoir,

1) h(x)=-x^4-2x^3+2x+1\\\\h'(x)=-4x^3-6x^2+2

2) (x+1)^2 ( -4x + 2)=(x^2+2x+1)(-4x+2)\\\\=-4x^3+2x^2-8x^2+4x-4x+2\\\\=-4x^3-6x^2+2\\\\=h'(x)

3) Etude du signe de la dérivée h'(x) = (x+1)²(-4x+2) et variation de h sur [-2;1]
Racines de h'(x) : (x+1)² = 0 ==> x+1=0
                                         ==> x = -1
                          -4x+2 = 0 ==> 4x = 2
                                         ==> x = 2/4 = 1/2

\begin{array}{|c|ccccccc||}x&-2&&-1&&\dfrac{1}{2}&&1\\ (x+1)^2&&+&0&+&+&+&\\ -4x+2&&+&+&+&0&-&\\ h'(x)&&+&0&+&0&-&\\ h(x)&-3&\nearrow&0&\nearrow&\dfrac{27}{16}&\searrow&0 \\\end{array}